CRIMINAL LAW ANALYSIS THE CRIME OF INCEST AND THE PSYCHOLOGICAL EFFECT OF THE VICTIM. - Akbar Farrel Herdiana; Akna Khoirun Nisa; Diandra Caroline Siagian; Nadya Raisha Putri; Nurul Ilmi Illahi (Problematika Hukum, 2022)
Incest refers to sexual or marital relationships between family members that are prohibited by law. Incest cases are often considered taboo and illegal and can have serious psychological and legal repercussions. the most common perpetrators of sexual violence, including incest, are fathers and uncles. Such as the case that occurred in Banyumas, Purwokerto in March 2023 last year. This is sad because many of the perpetrators of violence in the personal sphere are considered and expected to be protectors such as fathers, uncles, and husbands. Criminal responsibility for the perpetrators of incest can be charged with Article 287 of the Criminal Code or Article 419 of Law No.1 of 2023. Meanwhile, the formulation of incest against children can be charged using Article 294 paragraph (1) of the Criminal Code or Article 418 paragraph (1) of Law No.1 of 2023. In addition, the social-psychological impressions obtained by victims who experience incest will experience prolonged trauma. Social impressions are typical, namely that the child will be ostracized by his family, and discriminated against by the community. This article is written using normative and qualitative research methods that begin with an approach that focuses on analyzing applicable legal norms or regulations. The aim is to understand, explain, and interpret the written law. This research aims to assess the effectiveness of criminal law liability and child protection law in the decision and analyze the social sanctions obtained by the victim.Keywords: Incest; criminal code; child protection law; social sanction; psychological impact.